Physiological performance of yak under varying load carrying conditions - KATAKTALWARE, M A; POUROUCHOTTAMANE, R; RAJKHOWA, J; BORAH, B K D; BORAH, S; SARAVANAN, B C; SARKAR, M (The Indian Journal of Animal Sciences, 2011)
Effect of varying load on pack performance of yak was studied. Immediately after exercise, the values for all clinical parameters of animals carrying 30% load were significantly higher than 10 and 20% load groups and recovery tiIne was maximum in animals carrying 30% load. However, in general, no sign of fatigue was observed in any of the groups. The haematological parameters varied nonsignificantly and 35 min post-exercise the values of these haematological parameters reached to almost pre-exercise values in all the groups. On the basis of present study, it could be concluded that there was no adverse effect of load (up to 30%) on physiological performance of yaks.Â